Towards efficient biocatalysts: photo-immobilization of a lipase on novel lysozyme amyloid-like nanofibrils - Chaves, Analia Silvina (2016)
Herein, we report the preparation and characterization of a new biocatalyst based on the photo-immobilization of a lipase onto hybrid protein : sugar nanofibrils. The nanofibrils are obtained through the aggregation of hen white egg lysozyme induced by the highly sulfated glycosaminoglycan heparin. The new hybrid nanomaterial could be easily functionalized using photochemical reaction to attach lipases through dityrosine covalent bonds. Compared to the free enzyme, the photo-immobilized lipase has better thermostability and enhanced resistance to non-conventional environment. Structural and morphological characterization of the nanofibrils shows that they are compatible with amyloid-like aggregates. In addition, the supramolecular arrangement of heparin and lysozyme within the building unit of the nanofibrils is also proposed. The procedure reported herein could be useful to design a new generation of insoluble biocatalyst by a single photo-click step which is definitely cleaner and faster than conventional chemical cross-linked procedures.